2020
DOI: 10.3389/fendo.2020.00282
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast Growth Factor 19 Levels Predict Subclinical Atherosclerosis in Men With Type 2 Diabetes

Abstract: Objective: Fibroblast growth factor 19 (FGF19) plays an indispensable role in regulating bile acid, glucose, and lipid metabolism, and alterations of its circulating concentration is associated with the development of type 2 diabetes (T2D). Atherosclerosis is directly related to the death-deriving diabetic macroangiopathy in T2D, yet relationships between FGF19 and atherosclerosis in T2D remain unclear. The aim of this study was to investigate the association of circulating FGF19 levels with the development of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Activation of intestinal FXR stimulates the secretion of FGF15/19, which is later sensed by liver FGFR4 and inhibits the transcription of Cyp7a1/CYP7A1 , the rate‐limiting enzyme in the classical bile acid synthetic pathway and accounts for the suppression of the de novo synthesis of bile acids from cholesterol (Inagaki et al, 2005; Sayin et al, 2013). Moreover, the serum FGF19 level was found positively associated with the development of subclinical atherosclerosis in diabetic patients and with the serum TC level in patients with hypercholesterolaemia (Hu et al, 2020; Wu et al, 2021). The suppression of the enterohepatic FXR‐FGF15/19 signalling alleviated atherosclerosis, hypercholesterolaemia and obesity (Chen et al, 2016; Huang et al, 2019; Li et al, 2013; Wu et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Activation of intestinal FXR stimulates the secretion of FGF15/19, which is later sensed by liver FGFR4 and inhibits the transcription of Cyp7a1/CYP7A1 , the rate‐limiting enzyme in the classical bile acid synthetic pathway and accounts for the suppression of the de novo synthesis of bile acids from cholesterol (Inagaki et al, 2005; Sayin et al, 2013). Moreover, the serum FGF19 level was found positively associated with the development of subclinical atherosclerosis in diabetic patients and with the serum TC level in patients with hypercholesterolaemia (Hu et al, 2020; Wu et al, 2021). The suppression of the enterohepatic FXR‐FGF15/19 signalling alleviated atherosclerosis, hypercholesterolaemia and obesity (Chen et al, 2016; Huang et al, 2019; Li et al, 2013; Wu et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…FGF19 is also associated with type 2 diabetes mellitus (T2DM). T2DM patients often suffer from atherosclerosis, thus, understanding the underlying mechanisms involved in metabolism is crucial in understanding atherosclerosis, which may ultimately improve the development of T2DM [ 96 , 97 ]. Subclinical atherosclerosis is an early indicator of the onset of atherosclerosis, which could be examined by increased intima-media thickness (IMT) of arteries [ 98 ].…”
Section: Physiology and Clinical Significance Of Endocrine Fgfsmentioning
confidence: 99%
“…Subclinical atherosclerosis is an early indicator of the onset of atherosclerosis, which could be examined by increased intima-media thickness (IMT) of arteries [ 98 ]. A recent study found that serum levels of FGF19 were positively correlated with carotid IMT in men that showed that the level of FGF19 could be a predictor of subclinical atherosclerosis in men with [ 97 ]. Additionally, reports showed that the administration of NGM282, an analog of FGF19, has proven to be a protective factor for atherosclerosis [ 99 ].…”
Section: Physiology and Clinical Significance Of Endocrine Fgfsmentioning
confidence: 99%
“…In humans, some studies have investigated the relationship between circulating FGF19 and the presence of coronary artery disease (CAD), and have also proved the association between FGF19 and the development of major cardiovascular adverse events in stable CAD [4,5] . Our previous studies also showed that FGF19 could predict the progression of subclinical atherosclerosis in men with T2D [6] . In this study, we aimed to investigate the relationship between FGF19 and the risk of atherogenic dyslipidemia in patients with T2D and to explore whether FGF19 can be a biomarker for early diagnosis of atherogenic dyslipidemia in patients with T2D.…”
mentioning
confidence: 92%
“…[4,5] Our previous studies also showed that FGF19 could predict the progression of subclinical atherosclerosis in men with T2D. [6] In this study, we aimed to investigate the relationship between FGF19 and the risk of atherogenic dyslipidemia in patients with T2D and to explore whether FGF19 can be a biomarker for early diagnosis of atherogenic dyslipidemia in patients with T2D. [7] A complete physical examination was performed on each subject.…”
mentioning
confidence: 99%